Status of sunflower crop in Andhra Pradesh-Reasons for decline and measures to revive: STATUS OF SUNFLOWER IN ANDHRA PRADESH-REASONS FOR DECLINE AND MEASURES TO REVIVE - K VENKATARAMANAMMA; S NEELIMA; D LAKSHMI KALYANI; S JOSEPH REDDY (Journal of Oilseeds Research, 2019)
A survey was conducted to know the reasons for decline in area of sunflower and measures to revive the crop in six districts of Andhra Pradesh viz., Kurnool, YSR Kadapa, Prakasam, Ananthapuramu, Nellore and Chittoor districts. Among the different reasons explained, marketing problems, lack of stable yield in hybrids and diseases like necrosis are the major problems which prompted farmers to shift to other remunerative crops like cotton, Bengal gram, black gram, maize, red gram, groundnut and others in different districts of Andhra Pradesh based on their suitability. To bring back its cultivated area again some ofthe measures like development of promising hybrids, good marketing facilities, proper extension services and mechanization etc are needed.